Optimalisasi Motivasi Belajar Siswa Melalui Strategi Manajemen Kelas Guru Al-Qur’an Hadits di MAN 1 Kota Bima - Ismatu Rahmawati; Ruslan Ruslan; Kaharudin Kaharudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to describe the optimization of students’ learning motivation through classroom management strategies employed by Al-Qur’an Hadith teachers at MAN 1 Bima City. The primary focus is to obtain in-depth information regarding the forms of classroom management strategies implemented by Al-Qur’an Hadith teachers to optimize students’ learning motivation, students’ perceptions of the applied strategies, as well as the factors that support the success of these classroom management strategies. This research uses a qualitative approach with a descriptive research type. This approach was chosen because the researcher seeks to gain a deep understanding of the phenomena occurring in the field. The results of this study indicate that the classroom management strategies implemented by Al-Qur’an Hadith teachers consist of eight forms, namely: (1) structured lesson planning, (2) strengthening Qur’anic literacy at the beginning of the lesson, (3) management of classroom facilities and physical environment, (4) a personal approach through holistic attendance, (5) habituation of sholawat and strengthening of spirituality, (6) the use of varied teaching methods, (7) differentiated instruction according to students’ abilities, and (8) integration of Qur’anic stories with daily life. Students have a positive perception of the classroom management strategies implemented by the teachers. The factors influencing the success of these strategies include teacher personality, students’ readiness to learn, the school environment, and classroom rules or regulations. Based on the results of analysis and discussion, it can be concluded that classroom management strategies help teachers optimize students’ learning motivation. These strategies create a conducive and well-directed learning environment and encourage students’ active participation in the learning process. Thus, the implementation of classroom management strategies significantly contributes to improving students’ learning motivation at MAN 1 Bima City.